Archive Management System as Complementary Learning Media in the Digital Era - Andi Basuki; Madziatul Churiyah; Buyung Adi Dharma; Dewi Ayu Sakdiyyah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This research is a development research that aims to produce learning innovations in the psychomotor domain for practice in archival subjects. The research design adapts the Borg and Gall model which consists of eight stages, namely, (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) products testing, (7) product revision, (8) mass production. This research was conducted at the Office Administration Vocational School in Malang City. Data collection is done through filling out a questionnaire to determine the feasibility of the product being developed. The result of this research and development is a learning media called STELAR which is feasible and valid to be applied in the learning process, especially in the Office Administration Department. This is based on the results of the validation of material experts and media experts who obtained an average score of 93.53%, while from the test on students the results obtained 90%. Therefore, STELAR learning media can be used as an alternative learning media for practice in the Office Administration Department.